Informe preliminar: Limitantes y oportunidades del proceso de adopción y difusión de tecnologías forrajeras en Colombia - Enciso, Karen; Triana Ángel, Natalia; Díaz, Manuel Francisco; Burkart, Stefan (International Center for Tropical Agriculture, 2019)
The objective of this study is to identify limitations and opportunities in the process of development, adoption and dissemination of forage technologies in Colombia through an Agricultural Innovation System (AIS) approach. We have integrated qualitative approaches with the intention of providing a detailed analysis that addresses the nature of the inter-actor relationships and the contingencies that determine their changes. To do so, we rethink the processes of adoption and dissemination of forage technologies through a historical perspective, highlighting the many variables and actors involved in such processes. In this order of ideas, the following specific objectives were set out: (i) to identify at the historical level the main developments that have led the course of research and dissemination of forage technologies in the country; and (ii) map the actors that are part of the innovation system, describe their roles, links and attitudes of the agents involved. This document is part of a first delivery addressing the research and supply components of improved forage seeds. The perspectives of national and international scientists and research programs, as well as of professionals of multimillion-dollar companies are integrated here. First, a description of improved forages is presented as innovation technology of consideration. Second, a description of the release processes and adoption levels of improved forages in Colombia is provided. Third, the theoretical framework and methodology developed and used are explained. Later, the historical events and transformations that have affected the course of research and dissemination of forage technologies in Colombia are briefly described.